IMPLEMENTASI PRAKTIK PERDAGANGAN ADIL TERHADAP PEKERJA TEKSTIL PEREMPUAN DI SRI LANKA - Setyono, Kezia Regina; Elisabeth Dewi (Indonesian Association for International Relations, 2026)
This study investigates the implementation of fair-trade practices by Patagonia, with a focus on the treatment of female textile workers in Sri Lanka. It employs a qualitative research method using a case study approach and relies on secondary data. The analytical framework is based on the fair-trade principles established by the World Fair Trade Organization (WFTO), which emphasize economic justice, the protection of workers' rights, and the empowerment of women. The results indicate that women make up the majority of the textile sector in Sri Lanka. However, they are often marginalized as low-wage, non-technical workers, relegated to lower production roles with limited opportunities for economic advancement. There is a notable discrepancy between the fair-trade narrative promoted by Patagonia and the actual conditions faced by female workers in production. These findings suggest that the practices implemented by Patagonia and its supplier factories do not fully align with the core objectives of the WFTO's fair-trade principles